SenseHere: a born global start-up based in the UAE. Issue 4 (27th January 2016) - Rogmans, Tim
Abstract : Title: – SenseHere: a born global start-up based in the UAE. Subject area: – Management, strategy, entrepreneurship. Study level/applicability: – MBA, executive education. Case overview: – The case deals with the challenges of fundraising and location decision making for a high technology start up company based in the United Arab Emirates. Tan Rasab is a Chief Executive and co-founder of Sensehere, a high technology start up company involved in the design and development of semiconductors for wireless sensors. The company has developed a unique technology that allows sensors to dramatically reduce energy consumption and thereby improve battery life of sensors.The company is currently based in the UAE, where it finds the environment highly supportive overall but challenging from the point of view of fund raising. On the other hand in China the company is meeting significant investor interest and several partnerships have been concluded. Despite the advantages offered by the UAE environment, the company is considering moving some or all of its operations to China. Expected learning outcomes: – Familiarise students with the challenges of fundraising for new ventures.Understand the implications of technological breakthroughs in different application areas.Develop an understanding for the different considerations to be made when choosing a location for business functions. Supplementary materials: – Teaching notes.